The use of contrast-enhanced post Mortem CT in the detection of cardiovascular deaths. - Jonas Christoph Apitzsch; Saskia Westphal; Tobias Penzkofer; Christiane Katharina Kuhl; Ruth Knüchel; Andreas H Mahnken (PLoS ONE)
Objectives To evaluate the diagnostic value of contrast enhanced post mortem computed tomography (PMCT) in comparison to non-enhanced post mortem CT in the detection of cardiovascular causes of death (COD). Background As autopsy rates decline, new methods to determine CODs are necessary. So contrast enhanced PMCT shall be evaluated in comparison to established non-enhanced PMCT in order to further improve the method. Methods In a prospective study, 20 corpses were examined using a 64-row multisclice CT (MSCT) before and after intraarterial perfusion with a newly developed, barium-bearing contrast agent and ventilation of the lungs. The cause of death was determined in enhanced and unenhanced scans and a level of confidence (LOC) was given by three experienced radiologists on a scale between 0 and 4. Results were compared to autopsy results as gold standard. Autopsy was performed blinded to PMCT-findings. Results The method allowed visualization of different types of cause of death. There was a significant improvement in LOC in enhanced scans compared to unenhanced scans as well as an improvement in the detection of COD. The cause of death could be determined in 19 out of 20 patients. Conclusions PMCT is feasible and appears to be robust for diagnosing cardiovascular causes of death. When compared with unenhanced post-mortem CT intraarterial perfusion and pulmonary ventilation significantly improve visualization and diagnostic accuracy. These promising results warrant further studies.